Study to compare open surgery, endovenous thermal ablation and ultrasound guided foam sclerotherapy for treatment of varicose veins - Sandeep Raj Pandey (Society of Surgeons of Nepal, 2016)
Introduction and Objective: To compare open surgery, Endovenous thermal ablation(EVTA) and ultrasound(USG) guided foam sclerotherapy for primary superficial venous insufficiency(PVI) with respect to obliteration of superficial venous system at 3 months, clinical outcome and cost.